PENGARUH MEDIA KOMIK TERHADAP MINAT BACA SISWA KELAS IV SDN KEBOANANOM GEDANGAN - Alfi Rohmatis Suaidiyah; Danang Prastyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of using comic media on reading interest in grade 4 students at SDN Keboananom Gedangan. Interest in reading is an important factor in the success of learning and developing students' knowledge. The research design uses a Quasi Experimental Design in the form of a Nonequlvalent Posttest-Only Control Design. The research sample consisted of two groups of students, namely class IV-D a6s the experimental group which used comic media in the learning process and Class IV-B as the control group which used student textbooks and conventional methods. Data was collected through a questionnaire/reading interest questionnaire given after treatment. The data analysis technique used in this research uses the normality test, homogeneity test, and T-Test. This research was processed using IBM SPSS 22 for Windows. The results of hypothesis testing using the t-test state that the output results in the t-test column for equality of means show a sig value. (2-tailed) is 0.049, because the sig value. (2-tailed) 0.049<0.05 or a significant value smaller than 0.05. Ho is rejected, which means there is a difference. So t can be concluded that comic media has an impact on the reading interest of fourth-grade students at SDN Keboananom Gedangan.